Some measures for adaptation of Technical Vocational Education and Training to COVID-19 and prospects for its future development in Costa Rica - Vargas Méndez, Monserrat (2024)
The following article describes and analyzes some of the adaptive measures that were implemented by Costa Rican Technical Vocational Education and Training (TVET) institutions to address the problems and challenges that arose during the COVID-19 health crisis. Considering that TVET has a practical orientation and focuses on the development of work skills, we investigated, from a qualitative approach, which adaptation measures were implemented by the National Learning Institute (INA), the Ministry of Public Education (MEP), the University College of Cartago (CUC), the University College of Limón (CUNLIMÓN) and the National Technical University (UTN), and how some of these measures could be relevant in post-pandemic scenarios. Data collection was carried out through semi-structured interviews applied to the authorities of the aforementioned institutions in 2021 and the analysis of the data culminated in 2023. Among the most relevant results, it is highlighted that some of the actions implemented by the educational centers were decisively influenced by the weak conditions of educational investment (present in the system prior to the health crisis) and the availability of resources to reduce the negative effects of the pandemic. Measures to sustain virtual professional practices, as well as the implementation of curricula, became one of the main challenges to be solved. In this context, virtual practices and some curricular adaptations, specifically in evaluation and didactics, were part of the measures implemented during the period of confinement due to the pandemic.